Control of rep gene expression in plasmid pGA1 from Corynebacterium glutamicum - Venkova-Canova, Tatiana; Pátek, Miroslav; Nesvera, Jan (Journal of bacteriology, 2003)
The cryptic multicopy plasmid pGA1 (4,826 bp) from Corynebacterium glutamicum LP-6 belongs to the fifth group of rolling-circle-replicating plasmids. A determinant, which negatively controls pGA1 replication, was localized in the leader region of the rep gene coding for the initiator of plasmid replication. This region, when cloned into the compatible vector pEC6, was found to cause decrease of segregational stability of the pGA1 derivative pKG48. A promoter and a single transcriptional start site were found in the rep leader region in orientation opposite to the rep gene. These results suggest that a small countertranscribed RNA (ctRNA) (ca. 89 nucleotides in length), which might inhibit translation of pGA1 rep gene, is formed. Analysis of predicted secondary structure of the pGA1-encoded ctRNA revealed features common with the known ctRNAs in bacteria. Inactivation of the promoter P-ctRNA caused a dramatic increase of copies of the respective plasmid, which proved a negative role of the ctRNA in control of pGA1 copy number. A region between the promoters Prep and P-ctRNA with a potential to form secondary structures on both ctRNA and rep mRNA was found to cause low activity of the rep promoter even when promoter P-ctRNA was deleted. Thus, the sequence within the rep leader region itself seems to act, in addition to the ctRNA, as a second regulatory element of a novel type, negatively influencing expression of the pGA1 rep gene.
Keywords: plazmidy; bakteriální RNA; Corynebacterium; sekvence nukleotidů; Molecular Sequence Data; molekulární sekvence - údaje; konformace nukleové kyseliny; Base Sequence; DNA, Bacterial; DNA bakterií; Nucleic Acid Conformation; promotorové oblasti (genetika); Plasmids; RNA, Bacterial; regulace genové exprese u bakterií; Gene Expression Regulation, Bacterial; Promoter Regions, Genetic